Racismo estrutural no ensino de geografia - Ensino fundamental anos finais - Silva, Geovana Oliveira da (Universidade Federal de São Carlos, 2026)
The present research produces a reflection on the presence of structural racism in different forms and how it influences the school environment, highlighting Geography classes during the final years of Elementary School. Starting from the understanding that racism is the result of a long historical process that began in the colonial period, whose consequences are still manifested in the social, economic, political and educational relations of the country to the present day, they are perceptible when we analyze the experiences of students in the school environment, which make evident the presence of structural racism even in monitored environments. In this context, historical aspects that contributed to the consolidation of racial inequalities are analyzed during the research, evidencing how the black population was subjected to exclusion and marginalization even after the abolition of slavery, considering the geographical point of view in the face of racial themes, which weighs different points of analysis in different periods, an example being the process of elaboration of laws and documents aimed at the African and Afro-descendant population during the period of slavery to the present moment. In this way, it allows us to connect the influence of structural racism in educational documents such as the National Common Curricular Base (BNCC), highlighting the limitations that this document imposes in relation to the approaches to ethnic-racial relations in the teaching of Geography and the impacts of this absence on the critical formation of students. Throughout the research, we develop reflections on the presence of racism in everyday school life, manifested through prejudices, stereotypes and discriminatory practices that affect the construction of identity and the sense of belonging of black students. As a way of counteracting this reality, the research highlights the importance of pedagogical actions aimed at valuing African and Afro-Brazilian culture, strengthening black identity and encouraging respect for diversity. Through a qualitative approach, based on literature review and documentary analysis, it is concluded that education plays a fundamental role in combating structural racism, but it is still necessary to broaden the debates on ethnic-racial relations in the school environment to contribute to the formation of more critical, aware and committed citizens to the construction of a more just and inclusive society.
Structural racism in geography education – Upper elementary and middle school
Keywords: Colonização; Racismo estrutural; BNCC; Ensino de Geografia; Colonization; Structural racism; Geography teaching; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável